Transcriptome Analysis of Dauer Moulting of a Plant Parasitic Nematode, Bursaphelenchus xylophilus Promoted by Pine Volatile β-Pinene - Wei Zhang; Yongxia Li; Zhenkai Liu; Dongzhen Li; Xiaojian Wen; Yuqian Feng; Xuan Wang; Xingyao Zhang (Agronomy, 2022)
Pinewood nematode, Bursaphelenchus xylophilus, a pine-parasitic nematode, poses a serious threat to pine trees globally, causing pine wilt disease. When dispersal-stage juvenile 4 (dauer, JIV, a durable stage) of B. xylophilus enters the new pine, it transforms into a propagative adult (dauer moulting) and reproduces quickly. Our previous studies have found that pine-volatile β-pinene promotes dauer moulting of B. xylophilus; however, this mechanism is not clear. Here, this study is attempting to unravel the molecular process underlying dauer moulting of B. xylophilus through signal chemical tests and transcriptome analysis. The results showed that β-pinene could promote dauer moulting of B. xylophilus, while other common dauer moulting signals, such as dafachronic acid (DA), part of the TGF/insulin signal pathway, were inoperative. Moreover, the JIV soaked in 1% β-pinene for only 6 h could transform into adults at a significant rate. Therefore, the transcriptomes of JIV soaked in 1% β-pinene for 6 h were sequenced. It was found that 15,556 genes were expressed; however, only 156 genes were expressed differentially and enriched in the metabolism of xenobiotics, peroxisome, fatty acid metabolism, and carbon metabolism, indicating that energy metabolism was active at the early stage of dauer moulting. With a stricter parameter, the number of differential genes fell to 19, including 4 sterol hydroxylase, 5 dehydrogenase, 2 glucuronosyltransferase, 5 nuclear-related factor, 1 calcium-binding protein, 1 nitrogen metabolic regulation protein, and 1 cystathionine gamma-lyase. These results indicated that dauer moulting of B. xylophilus into adults might not be regulated by the TGF-β/insulin signal pathway but by another new signal pathway related to the 19 differential genes which need more exploration. Our results contribute to the understanding of the molecular mechanisms behind dauer moulting and may be useful in reducing pine wilt disease by suppressing this moulting to cut the life cycle of B. xylophilus.